Reduced Rating 30-pulse AC-DC Converter for Power Quality Improvement - Rohollah Abdollahi (Institute of Advanced Engineering and Science, 2017)
This paper presents the design and analysis of a novel polygon connected autotransformer based 30-phase ac-dc converter which supplies Direct Torque Controlled Induction Motor Drives (DTCIMD’s) in order to have better power quality conditions at the point of common coupling. The proposed converter output voltage is accomplished via three paralleled 10- pulse ac-dc converters each of them consisting of 5-phase diode bridge rectifier. An autotransformer is designed to supply the rectifiers. The proposed converter requires only three inter-phase transformers in the dc link that leads to the reduced kilovolt ampere rating, size, weight, and cost of the proposed rectifier. The design procedure of magnetics is in a way such that makes it suitable for retrofit applications where a six-pulse diode bridge rectifier is being utilized. The aforementioned structure improves power quality criteria at ac mains and makes them consistent with the IEEE-519 standard requirements for varying loads. Furthermore, near unity power factor is obtained for a wide range of DTCIMD operation. A comparison is made between 6-pulse and proposed converters from view point of power quality indices. Results show that input current Total Harmonic Distortion (THD) is less than 3% for the proposed topology at variable loads.